Inconsistências no Processo de Recomendação de Objetos de Aprendizagem utilizando Teoria de Estilos de Aprendizagem - Rodrigues, Ana Carolina; Assis, Luciana Pereira; Andrade, Alessandro Vivas; Pitangui, Cristiano Grijó; Silva, Cristiano Maciel (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
The Recommendation of Learning Objects and Learning Styles detection has attract interest from many researchers. This article describes the results achieved with the implementation of the Systematic Review of Literature, whose objective is to map the Learning Styles and Learning Objects. The results pointed out inconsistencies numerous in the way in which the educational resources are indicated to certain profiles of students, raising questions about the effectiveness of the Learning Styles in the process of recommendation of Learning Objects.